Ali je e-šport nova športna panoga? - Pisk, Jernej (Šport (Ljubljana), 2021)
With the development of digital information technologies, there has been an extraordinary boom in the competitive gaming of computer games. These were given the name esports more than a decade ago, as it is supposed to be a new sport. The best players are professionals who train and compete within their teams. The physical, mental and tactical preparation for the competitions is done by coaches and other experts who closely analyze the tactics of the opponents. The competitions are watched by crowds of fans, and millions of euros are turned over in the very drive of esports competitions. In short, esports are reminiscent of classic sports in many ways. We have already heard about the successes of Slovenian esports athletes in the daily sports reports on RTV Slovenia. Domestic and international esports federations are striving to include esports in the programs of major sports competitions, such as the Olympic Games. On the other hand, many have doubts about whether esports can really be equated with other sports. These and other issues excite the world of sport, and stimulate reflection on both sides. Last but not least, the answer to this question determines whether students should also encounter esports in school physical education, and whether esports should be included in the educational program of the Faculty of Sports. In this paper we highlight various aspects and point out the similarities and some significant differences between sport and esports.
Keywords: esport; e-šport; filozofija; olimpijske igre; olympic games; philosophy; physical education; sport; šport; športna vzgoja